ChemInform Abstract: Wavelength‐Selective Cleavage of Photoprotecting Groups: Strategies and Applications in Dynamic Systems. Issue 30 (July 2015) - Hansen, Mickel J.; Velema, Willem A.; Lerch, Michael M.; Szymanski, Wiktor; Feringa, Ben L.
Abstract Review: 49 refs.